COD fractions in raw and mechanically treated wastewater = Frakcje ChZT w ściekach surowych i mechanicznie oczyszczonych - Płuciennik-Koropczuk, Ewelina; Sadecka, Zofia; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents results of studies concerning the designation of COD fraction in the raw and mechanically treated wastewater in different year seasons. The research object was a mechanical-biological wastewater treatment plant with the output of >40 000 P.E., located in western Poland.
Keywords: ścieki surowe; frakcje ChZT; modele ASM; oczyszczanie mechaniczne; substancje biodegradowalne; substancje organiczne; raw wastewater; COD fractions; ASM models; mechanical treatment; substances biodegradable; organic substances